THE COMPARISON OF THE UNITED KINGDOM AND FRANCE ON AIRBNBâS MARKETING COMMUNICATION STRATEGY - Vanris Arya Saputra, Mochammad
The main goal of this particular research conducted by the researcher is to see whether there are any variance of differences between Generation Z that based their livinghood in the United Kingdom and France with the spotted factors of the eager to pick accommodation for holidays, their awareness towards the brand, and to see their point of view on how its marketing communication are doing, it is done to conclude the spiking variables within the traffic of the website. Methods that were used by the researcher were a mixed method, with the combination of both questionnaires with snowball sampling and a more personal interview with the participants. Five participants come from The United Kingdom, and the other five are coming from France. SPSS and ANOVA were used to analyse the data. It is to be found that some factors are affecting more than the other, such as: the rates of the accommodation, the opinions of other users, where its located, is it easy to be accessed, those are some of the dominant factors in making a decision to buy on the accommodations for holiday in both aforementioned countries. While in The United Kingdom they are more intrigued about pricing of the lodging, while in France they tend to pay more attention to the quality of the place. It is also discovered that in both countries they found out about Airbnb mostly through Facebook and other social media before they opened the website of Airbnb.